Long-term consequences of adolescent exposure to the synthetic cannabinoid AB-FUBINACA in male and female mice - Cristina Izquierdo-Luengo; María Ponce-Renilla; Marc Ten-Blanco; María Andrea Arnanz; Rosa María Tolón; Inmaculada Pereda-Pérez; Fernando Berrendero (iScience)
Summary: The consumption of synthetic cannabinoids during adolescence is reported to be a risk factor for the appearance of psychiatric disorders later in life. AB-FUBINACA is a member of the indazole carboxamide family of synthetic cannabinoids present in Spice/K2 preparations. The present study sought to investigate the long-term effects of AB-FUBINACA consumption during adolescence in both male and female mice. AB-FUBINACA revealed several sex-dependent behavioral alterations. In this sense, the administration of this synthetic cannabinoid in female, but not male, mice induced psychotic-like symptoms which were associated with changes in dendritic arborization and density of mature dendritic spines in pyramidal neurons of the prefrontal cortex, as well as with an up-regulation of differentially expressed genes in this brain area. This study helps to clarify the potential late detrimental effects of this potent synthetic cannabinoid that may derive from its use during adolescence.